Histopathological Change of Oral Malignant Tumour and Epithelial Dysplasia Subjected to Photodynamic Therapy - Masataka Uehara; Hisazumi Ikeda; Mihoko Nonaka, Izumi Asahina; Izumi Asahina (eJournal of Oral Maxillofacial Research)
Objectives: The purpose of this study is to analyze the morphological change of cell nuclei and the change of proliferating activity of oral malignancy and epithelial dysplasia between before and after photodynamic therapy in order to predict recurrence.Material and Methods: We experienced 14 cases of oral squamous cell carcinoma, one case of verrucous carcinoma and seven cases of epithelial dysplasia treated by photodynamic therapy (PDT). The mean nuclear area (NA) and coefficient of variation of the nuclear area (NACV) of 100 nuclei per slide were calculated using computer-assisted image analysis in hematoxylin and eosin stained biopsy specimens before and after PDT. Additionally, proliferating cell nuclear antigen (PCNA) immunohistochemistry was carried out in each specimen.Results: The mean NA after PDT was significantly lower than that before PDT in the nonrecurrent group. However, there was no significant difference in mean NA before and after PDT in the recurrent group. There were no significance differences in NACV before and after PDT in either the nonrecurrent or recurrent group. Furthermore, the PCNA labelling indices of the specimens after PDT was significantly lower than that before PDT in both the nonrecurrent and the recurrent group.Conclusions: Mean nuclear area in the biopsy specimen after photodynamic therapy is likely to be a predictive marker for the recurrence of oral squamous cell carcinoma or epithelial dysplasia subjected to photodynamic therapy, while coefficient of variation of the nuclear area and proliferating cell nuclear antigen labelling indices are less helpful in predicting the recurrence of such lesions.